How Generative AI Transforms Modern Office Work and Significantly Boosts Employee Productivity - Hamiduddin; Musdalifah (Journal Bisnis Digital dan Inovasi Manajemen, 2026)
The rapid integration of Generative Artificial Intelligence (AI) into the corporate landscape is fundamentally reshaping modern workplace dynamics. This article explores how Generative AI tools, such as automated content creators, smart assistants, and advanced data analytics, transform traditional office workflows. By automating routine and repetitive tasks, these technologies allow employees to focus on strategic, high-value, and creative endeavors, thereby significantly boosting overall productivity. However, this transition also introduces new challenges, including the critical need for employee upskilling and addressing ethical considerations regarding data privacy. Ultimately, this paper highlights that the successful adoption of Generative AI depends on a balanced collaboration between human ingenuity and machine efficiency, paving the way for a more agile and innovative future of work